How can weather index-based insurance protect farmers? - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
On 20-22 January, 2014, the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and the CGIAR Research Program on Policies, Institutions, and Markets (PIM) hosted a workshop on Mobilizing a CGIAR Agricultural Insurance Research Community. The workshop took place at the International Food Policy Research Institute in Washington, DC. Dr. Michael Carter of UC Davis spoke on the role of index insurance in managing risk and protecting farmers' livelihoods. Get his presentation: http://slidesha.re/1fg0Ga6